Gender differences in occupational preferences among young people: evidence from the UK - Scott, M (2019)
This thesis advances the understanding of gender differences in occupational preferences and job values among young people in the UK. There are two main aims; first, to provide an up-to-date description of gender differences. Second, to investigate how job values and occupational preferences are related, and to what extent gender differences are associated with parental education, mother, father, and sibling characteristics, or an individual’s own attitudes. My four chapters make several contributions to the literature. First, I explain the theoretical relevance of job values—the features of a job that are important to an individual, and describe differences by gender and parental education, in the UK and wider Europe. Second, I show how job values are associated with gender differences in preferences for science, technology, engineering and mathematics (STEM). Third, I examine the relationship between parental education and gender-typical occupational preferences and assess potential explanations for this. Fourth, I study the role of siblings, and whether preferences cluster within sibships. Overall, this thesis confirms the persistence of significant and substantial gender differences in occupational preferences in the UK. Gender differences in ratings on job values are small but important for occupational preferences; girls consistently value altruistic aspects of jobs highly and this discourages them from STEM aspirations. There are clear differences by parental education, with young people from a low parental education background more likely to have gender-typical aspirations. This is primarily due to the distribution of gender-typical occupations between occupational classes, and differences in the occupational class aspired to. Lastly, siblings do not significantly influence occupational preferences, either due to sibship composition, and/or through clustering of specific occupational preferences. Instead, the main between-family contrast is between only children and those who have siblings—the former are more likely to have gender-atypical aspirations.